Information about the All-Ukrainian Scientific and Practical Conference ‘Stress-Induced Immune Disorders and Their Consequences in Wartime’ - Problems of Cryobiology and Cryomedicine, Editorial Board (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(1):59-59